Time and money: substitutes in real terms and complements in satisfactions - Jens Bonke; Mette Deding; Mette Lausten (Levy Economics Institute of Bard College, 2006)
Time and money are basic commodities in the utility function and are substitutes in real terms. To a certain extent, having time and money is a matter of either/or, depending on individual preferences and budget constraints. However, satisfaction with time and satisfaction with money are typically complements, i.e., individuals tend to be equally satisfied with both domains. In this paper, we provide an explanation for this apparent paradox through the analysis of the simultaneous determination of economic satisfaction and leisure satisfaction. We test some hypotheses, including the hypothesis that leisure satisfaction depends on both the quantity and quality of leisure-where quality is proxied by good intensiveness and social intensiveness. Our results show that both the quantity and the quality of leisure are important determinants of leisure satisfaction, and, since having money contributes to the quality of leisure, this explains the empirical findings of the satisfactions being complementary at the same time as the domains are substitutes. Interestingly, gender matters. Intra-household effects and especially individual characteristics are more pronounced for women than for men for both domain satisfactions. Additionally, good intensiveness is more important for men (e.g., housing conditions), whereas social intensiveness is more important for women (e.g., the presence of children and participation in leisure-time activities).
Keywords: D1; D31; J22; 330; domain satisfaction; income distribution; leisure; gender